PRACTICAL APPROACHES TO REALIZATION OF THE SEISMIC RISK ANALYSIS METHODOLOGY FOR THE POTENTIALLY DANGER FACILITIES. SEISMOLOGICAL MONITORING - VYNNYCHENKO, O.; KACHALIN, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main practical approaches to stages realization of the seismic risk analysis methodology and evaluation of the natural and man-caused processes impact on the potentially dangerous facilities on the example of Ukrainian Nuclear Power plants in the aspects of seismic hazard territory are presented.